Agile Transformation in Digital Transformation Projects in the Automotive Industry in Germany and the Czech Republic : Strategies for Success - Al-Humssi, Rahmeh Ayman Tayseer; Kučera, Jan; Hájek, Stanislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
Abstract This master’s thesis examines Agile transformation in digital transformation projects within the automotive industry in Germany and the Czech Republic. To achieve this goal, a detailed literature review was conducted to explore Agile frameworks, leadership roles, transformation challenges, and performance measurement in structured environments. The theoretical findings were compared against insights from three expert interviews with Agile professionals working in the automotive sector. The interviews confirmed the need for context-driven framework adaptation, strong leadership involvement, and the importance of addressing cultural and organizational resistance. Based on these findings, a set of practical recommendations was developed and later validated by the interview participants. The main output of this thesis is the expert insights and the resulting recommendations for implementing Agile effectively in complex, traditional industries.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management of business informatics [obor dipl. práce]; diplomové práce; master's theses